1988
DOI: 10.1111/j.1751-0813.1988.tb14306.x
|View full text |Cite
|
Sign up to set email alerts
|

Infestation in the dog by the paralysis tick, Ixodes holocyclus — 4. Cardiovascular effects

Abstract: To determine the extent and significance of changes in heart rate and rhythm noticed previously in dogs paralysed with Ixodes holocyclus, two studies were undertaken. In one the electrocardiogram was recorded at stages throughout the disease and the traces analysed for changes, while in the second a detailed study of the effect of Ixodes holocyclus on the cardiovascular system was undertaken. The electrocardiographic changes were extremely variable between stages and between dogs. Generally, if a dysrhythmia o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
16
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…18 This finding, however, was not replicated in a more recent study of naturally occurring tick paralysis patients. Systemic hypertension was demonstrated in dogs experimentally infested with I. holocyclus and was attributed to central autonomic dysfunction causing excessive sympathetic stimulation.…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…18 This finding, however, was not replicated in a more recent study of naturally occurring tick paralysis patients. Systemic hypertension was demonstrated in dogs experimentally infested with I. holocyclus and was attributed to central autonomic dysfunction causing excessive sympathetic stimulation.…”
mentioning
confidence: 88%
“…Systemic hypertension was demonstrated in dogs experimentally infested with I. holocyclus and was attributed to central autonomic dysfunction causing excessive sympathetic stimulation. 18 This finding, however, was not replicated in a more recent study of naturally occurring tick paralysis patients. 15 Rather, the latter study demonstrated echocardiographic evidence of compromised cardiac function, primarily a reduction in the end-diastolic left ventricular dimension.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…Tick paralysis caused by the Australian paralysis tick ( Ixodes holocyclus ) is a progressive neuromuscular disease that also affects the cardiovascular, respiratory, gastrointestinal and central nervous systems . Reported fatalities approach 100% in untreated experimentally infested dogs .…”
mentioning
confidence: 99%
“…T ick paralysis caused by the Australian paralysis tick (Ixodes holocyclus) is a progressive neuromuscular disease that also affects the cardiovascular, respiratory, gastrointestinal and central nervous systems. [1][2][3][4][5][6][7][8][9][10][11] Reported fatalities approach 100% in untreated experimentally infested dogs. 4,12,13 Administration of a commercially available antiserum is central to the clinical management of tick paralysis, 12,14,15 but patients continue to die despite the use of antiserum.…”
mentioning
confidence: 99%